Global, regional and national burden of interstitial lung disease and pulmonary sarcoidosis, 1990–2021 and projection to 2040 - Zhang, Xinxin; Zhuang, Yanting; Xie, Yizi; Liao, Gang; Liang, Huiqiu; Wen, Wujin; Chen, Yuguang; Huang, Xiufang; Lian, Leshen; Qian, Xusheng; Zhan, Shaofeng (Frontiers in Medicine, 2025)
BackgroundInterstitial lung disease and pulmonary sarcoidosis (ILD&PS) represent a group of respiratory diseases characterized by high heterogeneity and substantial burden. In this study, we conducted a comprehensive analysis of burden with ILD&PS and provided estimates for 2040.MethodsPrevalence, incidence, disability-adjusted life years (DALYs), and deaths were analyzed at global, regional, and national levels using GBD 2021 data. Subgroup analyses were performed by age and gender to assess the quantity of global burden and trends. The BAPC model was used to forecast the worldwide disease load until 2040.ResultsFrom 1990 to 2021, global prevalence, incidence, DALYs, and mortality rates of ILD&PS increased by 128% (1887445.26 to 4306627.72), 148% (157,441.17 to 390,267.11), 169% (1,501,028.43 to 4,042,150.49), and 242% (54,967.23 to 188,222.37), respectively. Furthermore, the corresponding age-standardized rates (ASRs) also showed an upward trend. Additionally, the burden in Australasia and Andean Latin America varied greatly at the regional level, with ASRs burden increasing highest in high sociodemographic index (SDI) region over the previous 32 years. Correlation analysis revealed a positive correlation between ASR burden and SDI. Subgroup analysis showed a higher burden in adults over 50 and consistently greater burden in males than females.ConclusionThe overall burden of ILD&PS increased from 1990 to 2021, and by 2040, the ASRs burden were expected to progressively normalize. Policymakers should give prevention and treatment measures top priority, paying special attention to high-burden areas and populations.